Apicultura e fundos rotativos solidários: possibilidades em direção ao desenvolvimento territorial sustentável? - Silva, Misael Gomes da (2015)
Beekeeping has been used as means of increasing income for farmers in Zone of the South Forest of Paraíba State. This activity was financially supported by the Support Program (PAPPS) Revolving Fund Supportive, funded by the Ministry of Labour and Employment (MTE), too by the SENAES, as well as Bank of Northeast of Brazil (BNB), a policy of solidarity finance the "repayable", where the beekeeper gets the fund and has as fundamental element the investmentin beekeeping. The central objective of this study is to investigate possibilities for sustainable development of the territory with beekeeping that receives public funds. The research methodology is qualitative, based on field research in locus observations, in-depth interviews among more precisely between Settlements Tambaba and Nova Vida. With the arrival of the Revolving Fund Supportive, this activity had rise and, in this perspective we had as its central objective to verify possibilities of local territorial sustainable development from beekeeping as an alternative income producing, through this public policy. The cooperative of beekeepers of Paraíba - COOAP received this fund and invested among beekeepers, this fund, called "repayable" is not refunded to the bank, but needs to be redistributed among beekeepers